Ok, so I have this idea about infinity and its relationship with 0:
From hereon in, infinity will be referred to as INF.
From hereon in, any possible number will be referred to as x
x / INF = 0
x / 0 = INF
Therefore 0 * INF = x
0/INF = 0 * 1 / INF = 0 * 0 = 0
INF/0 = INF * 1 / 0 = INF * INF = INF
Also:
INF * x = INF
INF / x = INF
INF + x = INF
INF - x = INF
Just as:
0 * x = 0
0 / x = 0
0 + x = x
0 - x = -x
Also note that
x / INF = 0 * x
x / 0 = INF * x
Now, because x can be both positive and negative, let's say x is negative.
-x / INF = 0 (just as x / INF = 0)
-x / INF = x / -INF
Therefore, INF = -INF
It's a little cryptic, but I think you guys can get the gist...
What do you think?
2007-01-04
03:54:29
·
6 answers
·
asked by
Simplex Spes
2
in
Mathematics